Patrón espacial de la variabilidad molecular de Apis mellifera en Gran Canaria y La Gomera (Islas Canarias) - Muñoz, Irene (2011)
The Canary Islands have environmental conditions according to altitude, latitude and longitude, which influence in the distribution of organisms. Previous studies suggest the existence of honeybee (Apis mellifera L.) populations on the Canary Islands that have evolved relatively isolated and, therefore adapted to particular environmental conditions. Canarian honeybees were included in the African sublineage with Atlantic distribution (AIII), in which honeybee populations from the Macaronesian archipelagos (Azores, Madeira, the Savage Islands, Canary Islands and Cape Verde) and Portugal, are also included. In this paper we present the results of the molecular variation at mitochondrial DNA level of honeybee populations from Gran Canaria and La Gomera (Canary Islands). This marker is suitable for estimating genetic diversity and patterns of spatial differentiation in connection with the existing environmental variety on the islands of Gran Canaria and La Gomera.